Empowerment of Santri in Preventing Acute Respiratory Infections (ARI) through Education on Immune System Resilience and Herbal Processing - Suwito, Bambang Edi; Handayani, Handayani; Agustina, Titin Sholihah; Setiawan, Tirta Akbar Putra; Maula, Elqisha Avatry; Aviciena, Raditya Ahmad; Andriansyah, Ahmad Istan; Firdaus, Farhan Zidany; Azzahra, Aslin Nuroniyah; Imansyah, Atha Zaky; Berliyani, Jella; Rodhiyana, Rosda (UKInstitute, 2026)
comprehensive education on ARI prevention. The program involved 20 female santri and was implemented through a series of activities, including counseling, practical training in herbal processing, and the initiation of a Family Medicinal Plant (TOGA) garden. Evaluation results show a significant increase in knowledge, proven by an average post-test score increase of 6.5% and a shift in knowledge classification to the